King Midas and the golden touch - Hewitt, Kathryn; Hawthorne, Nathaniel, 1804-1864. (San Diego : Harcourt Brace Jovanovich, 1987)
A king who wishes for the golden touch is faced with its unfortunate consequences.
School Library Journal.
4.1
K-3
Keywords: Midas (Legendary character) -- Juvenile literature; Midas (Legendary character); Mythology, Greek; Midas; Classical mythology; Mythology, Greek; Folklore